Assessing the Level of Awareness about Malnutrition and Poor Drinking Water Affecting Child Health in District Chiniot, Punjab, Pakistan - Mahmood, Babak; Hussain, Shabbir; Sohail, Malik Muhammad; Hussain, Nisar; Ahmad, Muhammad (Pakistan Journal of Nutrition, 2013)
This study investigates the level of awareness about malnutrition and poor drinking water on the child health in Chiniot. Lack of improved drinking water and sanitation services causes major diseases like diarrhea affecting health status and mortality among children. Using a quantitative data, the study’s major objective was to determine whether access to improved sources of water and nutrition in Chiniot are affective for health of children who are less than five years of age. Potential mechanism behind the relationships between child health and different types of water supply and sanitation services are also explored. Data were collected from different villages of Chiniot. Multi-stage sampling technique was used to collect a sample of 200 respondents. Interview schedule was used as a tool for data collection. The main objectives of this study were to study the awareness of rural people about the effects of malnutrition and poor water supply on child health. The major findings of this study are that mostly people in rural settings have not awareness about malnutrition, poor drinking water and children health. Mostly people are less educated and pay no attention on children health.